The factors impacting the intermediating variable of employee engagement toward employee performance in a hybrid working model - Chanapa Jindain; Bhumiphat Gilitwala (Rajagiri Management Journal (RAMJ), 2024)
Purpose - The purpose of this study was to investigate the factors impacting the intermediating variable of employee engagement toward employee performance in a hybrid working organization in Bangkok, Thailand. Design/methodology/approach - This study uses secondary data analysis and an archival study; the primary data were gathered from 370 employees who are working in a hybrid model environment in a private agricultural machinery company. To construct a new conceptual framework, this study adopted four frameworks from the previous research. Findings - Perceived organizational support and trust and respect in the organization are found to have a significant positive impact on employee engagement. Moreover, there is a significant positive impact of the employee engagement on employee performance in a hybrid working model. Research limitations/implications - For hybrid work environments, the research focused mainly on the emotional themes of perceived support, trust and respect in the organization. Therefore, there would be many factors that could possibly affect those dependence variables in any environment, which will have to be investigated more in future research. Either in the organization or in the company, many departments and business units operates for the company, but the researcher specifies only the business units or departments that now use the hybrid working model. Practical implications - This study focuses on a case study of an agricultural machinery company, which likely produces different results than other industries, other industries may produce different results. Social implications - Hybrid working models can blur the boundaries between work and personal life, potentially leading to increased stress and burnout. Organizations should prioritize work-life balance and employee well-being by promoting flexible schedules, encouraging breaks and time off, and providing resources for mental health support. Originality/value - The organization which is operating among a hybrid working model, the increasing of perceived organizational support and trust and respect level, has positively increase the employee engagement toward enhancing the employee performance.
Keywords: 650; Employee engagement; Employee performance; Perceived organization support; Trust and respect; Hybrid working model